Assessing the impact of nitrogen regulatory policies on fertilizer use and food production elasticity - Tirgariseraji, Mohammad; Nejadhashemi, A. Pouyan; Sabouhi Sabouni, Mahmood; Jafari, Yaghoob; Persson, Tomas; Mirzabaev, Alisher; Nikouei, Alireza; Moller, Kieron; Shahnoushi Foroushani, Naser (Elsevier, 2025)
Food production is the primary source of nitrogen pollution, which has significantly impacted the nitrogen cycle and exceeded the nitrogen-safe operation space of the planet. The objective of this study is to assess the effectiveness of the Nitrogen Regulatory Policy (NRP) in reducing nitrogen fertilizer use under population pressure for meat, dairy, wheat, and potatoes in the Zayandeh-Rud River basin, Iran. The methodology of this study involves two main components. First, an elasticity criterion was formulated to assess the trade-off between nitrogen fertilizer use and food production capacity. This criterion integrates optimized cropland, the Block of Distributed Calories (BDC), and nitrogen fertilizer use, with food production capacity quantified in terms of the BDC at its optimal level. Second, the simulated distribution of the elasticity criterion was analyzed using Simulation and Econometrics to Analyze Risk (Simetar), defining elastic and inelastic zones to capture the variability in the trade-off under different conditions. The results of this study identified key factors influencing the elastic and inelastic ranges of the elasticity criterion, including technological change, the weight of diet components in dietary preferences, and the diminishing returns of the NRP. The NRP solution aims to reduce nitrogen fertilizer use by targeting a lower application range. It addresses the challenges of fertilizer management under population pressure, specifically for farming systems in the Zayandeh-Rud River basin operating at the ‘diminishing marginal production’ stage. The trade-off between livestock and non-livestock diet components enhances nitrogen fertilizer efficiency under population pressure as long as livestock components remain within the elastic zone and non-livestock components stay within the inelastic zone. The novelty of this study lies in the introduction of the elasticity criterion for nitrogen fertilizer use under population pressure. This innovative metric highlights the risk of ineffective trade-offs between food production capacity and nitrogen fertilizer adjustments, offering a crucial tool to guide sustainable agricultural practices within the defined criterion ranges.